Efecto de una metodología basada en la Plataforma “Web Jungle English” en el nivel de desarrollo del aprendizaje gramatical del idioma inglés de los estudiantes del I y II Ciclo de la Escuela Profesional de Idiomas de la UNSM – T, 2019 - Ruiz Rodriguez, Frank Jordan (2020)
This research aimed to determine the effect of a methodology based on the web platform "Jungle English" on the development level of grammatical learning of the English language of students of the I and II cycle of the Professional School of Languages of the National University of San Martin - T, 2019. The type of research was applied with an experimental level and a pre-experimental design with pre- and post-test. The sample consisted of 38 students. The instrument used consisted of 118 questions based on grammatical content. The results showed that the level of development of grammatical learning before the application of a methodology based on the "Jungle English" web platform was deficient, since 55% of the students (21) had grades between 0 and 10. Likewise, the level of development of grammatical learning after the application of a methodology based on the "Jungle English" web platform was optimal, since 47% of the students (18) had grades between 16 and 20. It is concluded that the methodology based on the web platform "Jungle English" has a positive effect on the level of development of grammatical learning in the students of the I and II cycle of the professional school of languages of the UNSM-T, since the significance value (0.000) is less than 0.05. Likewise, it is important to mention that the effect is determined because the Tc (6.825) is greater than the Tt (2.042), thus accepting the alternative hypothesis of the research.